2018
DOI: 10.1038/s41598-018-35290-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical mechanisms of oceanic mantle earthquakes: Comparison of natural and experimental events

Abstract: Because they provide information about the spatial distribution of brittle deformation, both seismologists and experimentalists use b-values to study earthquake populations. Here, we present the b-values for intermediate-depth intraslab earthquakes in the Pacific slab beneath the Tohoku and Hokkaido regions, northeastern Japan and find a difference in the lower-plane event b-values in the double seismic zone. Lower-plane events reveal significantly larger b-values beneath Tohoku (0.96) than Hokkaido (0.86), im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 65 publications
(100 reference statements)
4
34
0
Order By: Relevance
“…Large and small earthquakes present striking similarities (e.g. Kita & Ferrand, 2018;Ide, 2019;Brodsky, 2019) and appear to nucleate similarly (Ide, 2019;Abercrombie, 2019), which supports that laboratory analogues (e.g. Mw -6, fault = 1mm; Ferrand et al, 2017) may be representative of natural processes (e.g.…”
Section: Accepted Articlesupporting
confidence: 54%
“…Large and small earthquakes present striking similarities (e.g. Kita & Ferrand, 2018;Ide, 2019;Brodsky, 2019) and appear to nucleate similarly (Ide, 2019;Abercrombie, 2019), which supports that laboratory analogues (e.g. Mw -6, fault = 1mm; Ferrand et al, 2017) may be representative of natural processes (e.g.…”
Section: Accepted Articlesupporting
confidence: 54%
“…Previous studies have found large b value anomalies near the top of some slab segments (Katsumata, ; van Stiphout et al, ; Wiemer & Benoit, ; Wyss et al, ); our results suggest that these differences are systematic, may be controlled by a few physical parameters, and are a global feature. Recent work in Japan (Kita & Ferrand, ) show larger b values in Hokkaido along the USL but have lower b values in the Tohoku area. Our results do not have the resolution to be able to compare each segment but point toward a global systematic behavior of b values between USL and LSL.…”
Section: Frequency‐magnitude Statisticsmentioning
confidence: 90%
“…The microfractures are likely precursors of the mesoscale fractures. These dehydration reactions indicate that high INTRODUCTION High-pressure (HP) brittle deformation of subducting slabs has recently drawn increasing attention through petrological (e.g., Angiboust et al, 2012;Scambelluri et al, 2017;Behr et al, 2018), experimental (e.g., Okazaki and Hirth, 2016;Ferrand et al, 2017) and geophysical investigations (e.g., Kita and Ferrand, 2018;Florez and Prieto, 2019). HP brittle deformation is often correlated to an important facies change from blueschist to eclogite as it is coupled with significant metamorphic dehydration reactions (Peacock, 1993;Gao and Klemd, 2001;Hacker et al, 2003;Austrheim and Andersen, 2004).…”
mentioning
confidence: 99%